2017
DOI: 10.1007/s10571-017-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Mitochondria-Associated ER Membranes (MAMs) in Traumatic Brain Injury

Abstract: The endoplasmic reticulum (ER) and mitochondria have both been shown to be critical in cellular homeostasis. The functions of the ER and mitochondria are independent but interrelated. These two organelles could form physical interactions, known as MAMs, to regulate physiological functions between ER and mitochondria to maintain Ca, lipid, and metabolite exchange. Several proteins are located in MAMs, including RNA-dependent protein kinase (PKR)-like ER kinase, inositol 1,4,5-trisphosphate receptors, phosphofur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…Along with the evidence that miR-132/212 was consistently downregulated in AD [24], it is reasonable to speculate that miR-212 may act like a bridge between TBI and neurodegenerative diseases. Moreover, there is a consensus that crosstalk widely exists between ferroptosis and other forms of regulated cell death [53,[63][64][65][66], and emerging evidence indicates that miR-212 may prevent neuron death by inhibiting other target genes, like Sirt2 [67] or participating in other pathways, like autophagy [65,66] or apoptosis [63]. Further studies are urgently required to identify whether miR-212-5p is involved in any other pathologic process of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the evidence that miR-132/212 was consistently downregulated in AD [24], it is reasonable to speculate that miR-212 may act like a bridge between TBI and neurodegenerative diseases. Moreover, there is a consensus that crosstalk widely exists between ferroptosis and other forms of regulated cell death [53,[63][64][65][66], and emerging evidence indicates that miR-212 may prevent neuron death by inhibiting other target genes, like Sirt2 [67] or participating in other pathways, like autophagy [65,66] or apoptosis [63]. Further studies are urgently required to identify whether miR-212-5p is involved in any other pathologic process of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The TBI-induced neuronal death has been commonly delineated into two different categories: necrosis in the primary phase and apoptosis in the secondary phase. There are many forms of apoptosis, such as intrinsic apoptosis, extrinsic apoptosis, mitochondrial apoptosis, endoplasmic reticulum (ER)-associated apoptosis, and the iron-related apoptosis (ferroptosis), all of which can be observed be used as therapeutic target after TBI 5,6 . In addition, necroptosis, a recently discovered form of necrosis, is demonstrated to be a programmed cell death and participates in secondary neuronal cell death after TBI 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of TBI is unclear, several previous studies have demonstrated the involvement of oxidative stress and apoptosis (Cheng et al, 2016;Liu et al, 2018). Several signaling pathways are involved in regulating oxidative stress after TBI (Sun et al, 2017;Fu et al, 2018). Nrf2 signaling pathway is activated after oxidative stress to regulate downstream target genes, such as HO1 (Hall et al, 2018;Zhang and Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%